Isolation and Characterization of The Functional Properties of The Major Protein Fraction from Nyamplung (Calophyllum inophyllum) - Muhammad Prima Putra; Pudji Hastuti (Indonesian Food and Nutrition Progress, 2014)
Defatted nyamplung (Calophyllum inophyllum) seeds as by-products of oil extraction is a rich source of protein. In order to evaluate its potential as value-added of nyamplung seeds, nyamplung proteins were isolated by solubilization-precipitation method at pH 3 and 5. The obtaining protein isolates were characterized with respect to their functional properties, including water binding capacity, oil binding capacity, foaming capacity, foaming stability, emulsifying activity, emulsifying stability, gelation capacity, and amino acid composition. The results show that nyamplung protein could be considered as high protein quality because essential amino acids leucine (4.39 %), proline (4.22 %), valine (3.34 %), aspartic acid (3.23 %) and lysine (3.34 %) were found to be the major amino acids. Polar amino acids were higher than non-polar amino acid (1.7 times). With the consequence in higher ratio of water binding capacity to oil binding capacity (2.7 times) and high value of hydrophile-lypophile balance. In general, the isolated protein from precipitation at pH 3 (IP3) was found to have better functional properties than that being precipitated at pH (IP5), and showed excellent in water binding, emulsifying, gelation and foaming properties. In conclusion, IP3 can be utilized as high quality proteins and emulsifier in oil in water emulsion system.